REPSOL oil spill off Central Perú in January 2022: a modeling case study - Espinoza Morriberón, Dante (2023)
This study simulates the spillage of 1460 metric tons of oil that occurred in January 2022 off La Pampilla Refinery, in central Perú. The oil slick was predominantly displaced northward along the coastline, driven by prevailing currents and winds in the region. The weathering analysis revealed that the removal of oil was mainly due to evaporation (28%) and beaching processes (70%) within 96 h after the initial release. The coastal areas spanning from Ventanilla to Punta Chancay experienced significant impacts from the oil spill, representing 96% of the total affected coastal extent. Specifically, Ventanilla and Santa Rosa Beaches and the National Reserve System of Islands were heavily impacted during the first 24 h, while the surroundings of Ancon ´ Bay, Aucallama and Pasamayo beaches were affected after two days. This modeling case study provides valuable insights into the fate and transport of the Repsol oil spill.